AB1206 SELF-REPORT OF FRACTURE HISTORY COMPARED TO FRACTURE CODES FROM AN ELECTRONIC HEALTH RECORD DATASET. (June 2019) - Danila, Maria; Mudano, Amy; Rahn, Elizabeth; Lacroix, Andrea; Curtis, Jeffrey; Saag, Kenneth
Abstract : Background: Self-reported fracture history data is frequently used in epidemiological studies of osteoporosis. Self-reported fracture data may differ from fracture history coded in electronic health records (EHR) due to imperfect patient recall, incomplete communication with clinicians, or lack of a universal EHR. Because both self-reported fracture history and EHR data can define phenotypes for clinical research studies, it is important to understand how these 2 data sources compare. Objectives: To compare self-reported fracture history using survey data with fracture codes from an available EHR dataset. Methods: Self-reported fracture data was derived from the Activating Patients at Risk for OsteoPOroSis (APROPOS) trial, which recruited participants from the Global Longitudinal study of Osteoporosis in Women (GLOW) cohort. Prior fracture data was collected using a survey deployed June - August 2015. Women were asked if they ever had a fracture and for each fracture type the date of the most recent one. Data on fractures recorded in the EHR September 2011 - June 2015 was obtained from Kaiser Permanente Washington Health Research Institute. We excluded skull, toes and fingers fractures. We defined concordance between the EHR and self-reported data if the location of a fracture was reported to be the same and if the reported dates were within 1 year of each other. Kappa (κ) statistic described the concordance between the 2 sources of fracture history. Descriptive statistics evaluated potential factors associated with discordance between the self-reported and EHR-coded fracture history. Results: A total of 133 fractures from 360 women (91% white, mean[SD)] age 74.5(7.5) years, 82% had some college education) were included. There were 35 fractures reported on the survey but not in the EHR and 39 fractures coded in the EHR but not in the survey. Agreement between self-reported and EHR fractures was κ 0.48. Of the discordant fractures, we were more likely to find claims for fractures in EHR referent to self-report among whites (OR=5.5, 95%CI 1.1-27.9), for major osteoporotic fractures (OR=2.8, 95%CI 1.1-7.1), and for fragility fractures that typically require hospitalization (vertebral, hip, femur, pelvis) (OR=3.8, 95%CI 1.3-10.7). Discordance between EHR codes and self-reported fractures did not vary by age, formal education, or health literacy. Conclusion: There was only modest correlation between self-reported fracture history and EHR fracture codes. This discrepancy may have implications for clinical and epidemiological studies of fractures suggesting that combining both types of data may be optimal. Disclosure of Interests: Maria Danila Grant/research support from: Pfizer, Inc., Consultant for: Sanofi Genzyme & Regeneron, Amy Mudano: None declared, Elizabeth Rahn: None declared, Andrea LaCroix: None declared, Jeffrey Curtis: None declared, Kenneth Saag Grant/research support from: Amgen, Ironwood/AstraZeneca, Horizon, SOBI, Takeda, Consultant for: Abbvie, Amgen, Ironwood/AstraZeneca, Bayer, Gilead, Horizon, Kowa, Radius, Roche/Genentech, SOBI, Takeda, Teijin